An hPSC-Derived Tissue-Resident Macrophage Model Reveals Differential Responses of Macrophages to ZIKV and DENV Infection - Jianshe Lang (Stem Cell Reports, 2018)
Summary: Zika virus (ZIKV) and dengue virus (DENV) are two closely related flaviviruses that lead to different clinical outcomes. The mechanism for the distinct pathogenesis of ZIKV and DENV is poorly understood. Here, we investigate ZIKV and DENV infection of macrophages using a human pluripotent stem cell (hPSC)-derived macrophage model and discover key virus-specific responses. ZIKV and DENV productively infect hPSC-derived macrophages. DENV, but not ZIKV, infection of macrophages strongly activates macrophage migration inhibitory factor (MIF) secretion and decreases macrophage migration. Neutralization of MIF leads to improved migratory ability of DENV-infected macrophages. In contrast, ZIKV-infected macrophages exhibit prolonged migration and express low levels of pro-inflammatory cytokines and chemokines. Mechanistically, ZIKV disrupts the nuclear factor κB (NF-κB)-MIF positive feedback loop by inhibiting the NF-κB signaling pathway. Our results demonstrate the utility of hPSC-derived macrophages in infectious disease modeling and suggest that the distinct impact of ZIKV and DENV on macrophage immune response may underlie different pathogenesis of Zika and dengue diseases. : In this article, Tang and colleagues demonstrate the utility of hPSC-derived tissue-resident macrophages in infectious disease modeling and show differential responses of macrophages to ZIKV and DENV infection. ZIKV-, but not DENV-, infected macrophages exhibit prolonged migration and express low levels of pro-inflammatory cytokines and chemokines by disrupting the NF-κB-MIF positive feedback loop via inhibition of the NF-κB signaling pathway. Keywords: human pluripotent stem cells, macrophage differentiation, Zika virus, dengue virus, dissemination, immune response, NF-κB signaling, macrophage migration, MIF, disease modeling